Improving Problem Solving Skills through Problem Based Learning (PBL) for Students at SMAN 1 Jogorogo - Agustina Fajar Rini; Wasilatul Murtafiah; Rini Setyowati (Lembaga Pendidikan Hikmatun Najah Blora, 2023)
The implementation of the â€œMerdekaâ€ curriculum requires students to have high-level thinking skills such as problem-solving skills. However, in reality, this is in contrast to the studentsâ€™ability in solving the real problem. The purpose of this study is to describe the effect of the Problem Based Learning (PBL) model in improving students' problem-solving skills. The Problem Based Learning is a learning model that syntaxes on the problem-solving process, so that students are able to provide solutions and familiarize themselves with the skills of problems analysis, collaboration, communication, creativity and critical thinking. Problem solving indicators that will be measured are connecting information/data to understand the problem, evaluating alternative problem solving presented, and making a design to solve the problem. This research is a Classroom Action Research (CAR) which took place in SMAN 1 Jogorogo with the subject of tenth grade (XA) students totaling 40 on the material of environmental change. The data were collected through observation, written test Daily Test (DT) and documentation which were then analyzed through comparing the average results of each indicator. The results showed that the initial data regarding the indicator of connecting information/data to understand the problem was 76.8%, increased in the first cycle to 82.2%, and in the second cycle to 86.25%. The indicator of evaluating alternative problem-solving initial data was 77.5%, increased in the first cycle to 85% and the second cycle to 87.5%. The indicator of making a design to solve the problem in the initial data was 80% and increased to 82.5% in the first cycle and 85% in the second cycle. From the various explanations above, it shows studentsâ€™ problem solving skills has increased as seen from the Daily Test (DT) scores. Keywords: Problem Based Learning (PBL), problem solving, Classroom Action Research (PTK). Environmental Change.